Culture of Sambatan in the Midst of Modernization in Air Putih District, Batubara Regency - Manugeren, M.; Mahid, Perveen Sonia; Pardi, Pardi (International Journal of English and Applied Linguistics (IJEAL), 2023)
This research is motivated by the existence of the sambatan culture carried out by the Javanese people outside their original area until now with the aims to explore and describe the sustainability and shifting values of the sambatan culture in Air Putih District, Batubara Regency in the midst of modernization through qualitative research with data collection techniques in the form of interviews, observations and document studies. The technique for determining sources or informants is the snowball technique. The theory used is the theory of social change and semiotics. Data analysis refers to the analysis method of Miles, Huberman and Saldana by triangulating methods and data sources to test the validity of the data in drawing research conclusions. The results of the study show that there are values of mutual cooperation, volunteerism, kinship, solidarity and empathy, social equality, altruism, social identity and trust in the Sambatan culture. Modernization that has changed the mindset and life of rural communities has had an impact on the shifting values of the sambatan culture marked by causal factors such as the emergence of wages, individual nature, increasing economy and the availability of experts.